Empowering rural women's involvement in income generating activities through BRAC microfinance institution in Sylhet District, Bangladesh - Akter, Aysha; Ahmad, Nobaya (Human Resource Management Academic Research Society, 2020)
This article presented the findings on the role of microcredit financial assistance, specifically from Bangladesh Rural Advancement Committee (BRAC) Micro-finance institution to assist rural women in Sylhet District, Bangladesh involved in income generating activities. The impact on their socio-economic empowerment, the constraints of rural women in having access to loan service from micro-finance institutions and loan repayment process will be discussed. The target population of the study was those women who had availed microcredit facilities from some microcredit providing institutions or organizations in the study area. Survey method was used as a technique for data collection. The results of the analysis indicate that participation of rural women in micro-finance assisted income generating activities contributes towards socioeconomic empowerment. It also showed that most of the rural women who availed the facility of microcredit finally became empowered through acquiring the confidence level, business skills, decision making power, and self-esteem. The findings also showed that microcredit has significant impact on the up lift of socio-economic empowerment of the women’s in Sylhet district. However, constraints of rural women in accessing loan and loan repayment process should be properly addressed by the stakeholders to improve the contribution of micro- finance institutions for achieving sustainable development goal. Hence, accessing microcredit has been able to empower women financially and it is suggested that microcredit loan be made accessible to poor women who are keen to uplift the family’s economic wellbeing.